Desafios dos docentes na prática pedagógica de cursos técnico - Souza, Sueli Maria Lopes Galvão de (2021)
Teaching, throughout history, brings in its essence a unique beauty and many challenges for those who see it as a practice that promotes the realization of dreams, the transformation of people and society. The objective of this research was to identify the challenges of pedagogical practice and train the teachers at Senac Itapetininga. This is a study with a qualitative approach, of an exploratory-descriptive nature. As a methodological tool, the focus group technique was used as an instrument for data collection, in which the guiding questions were focused on the didactic and pedagogical difficulties of the teachers. The conversation was recorded and then transcribed to enable content analysis according to Laurence Bardin, with thematic criteria and categorization of results. Afterwards, there was the training with the Problematization Method with the Arch of Maguerez, through which the problem related to learning gaps/difficulties brought by the students was studied. There were 20 hours of synchronous and asynchronous activities. In the assessment of training, the professors pointed out that many learnings can be aggregated and applied in the context of the classroom, in the development of Curricular Units and, with this, expand the ways in which students learn, stimulating initiative, protagonism and construction collective and creative for the problems experienced, in addition to being able to respond in greater depth to the challenges of teaching and of today's society